Analisis Kecelakaan Kerja Dalam Upaya Menurunkan Kecelakaan Kerja Menggunakan Metode Fault Tree Analysis Di UMKM Kopi 1000 Nurhidayah - Rizal Syarifuddin; Andrie Andrie; Ramli Ramli; Ariangga Dwy Sakti R (Universitas Mercu Buana, 2022)
Work accidents are one of the most common problems in companies where these accidents often occur in workers and cause severe injuries at the physical level of workers. UMKM Kopi 1000 Nurhidayah in carrying out activities cannot avoid problems that will occur, the purpose of this study is to find out the causes of work accidents that occur and provide solutions to the causes of these events. This type of research is qualitative and quantitative with primary and secondary data using the Fault Tree Analysis (FTA) method. Work accidents in UMKM Kopi 1000 Nurhidayah occur due to human factors, equipment factors, work procedures, and environmental factors. The types of accidents are falls, pinched hands, earaches, backaches, shortness of breath, tightness, eye pain, and blistered hands. The highest cause of accidents was coffee slime with a probability of 7.74% and the lowest was a work shirt with holes and broken glasses with a probability of 0.92%. The solution to the cause of work accidents is to prepare yourself physically and mentally, by periodically replacing damaged personal protective equipment to minimize the impact of work accidents, as well as the need to conduct training on safety standardization, and always maintain a clean work environment.